2011
DOI: 10.1097/mao.0b013e3181ff7562
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Translabyrinthine Approach With Transapical Extension in the Management of Giant Vestibular Schwannomas

Abstract: Results indicate the enlarged translabyrinthine approach with transapical extension as an elective approach for removal of giant VS. The method permits achievement of a high rate of total removal with low incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
0
30
1
Order By: Relevance
“…Several authors have reported that TLA and the retrosigmoid approach are two major surgical options for the removal of a large or giant VS [2,3,5,7,9,28,29]. In our department, TLA is used to remove all kinds of VSs where hearing preservation is not essential, while the retrosigmoid approach is only used to remove a VS of <20 mm with hearing level in class A or B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported that TLA and the retrosigmoid approach are two major surgical options for the removal of a large or giant VS [2,3,5,7,9,28,29]. In our department, TLA is used to remove all kinds of VSs where hearing preservation is not essential, while the retrosigmoid approach is only used to remove a VS of <20 mm with hearing level in class A or B.…”
Section: Discussionmentioning
confidence: 99%
“…There are several authors who have reported their successful experience with removal of large or giant VSs via the translabyrinthine approach (TLA) in large series [2,5,6,7,8]. Also, it is difficult to achieve a postoperative functional outcome in large or giant VSs which is as good as that observed in small or medium VSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications included the translabyrinthine-transapical exposure described by Angeli et al 2 in which the IAC is opened with greater than 300° of exposure, or the combined translabyrinthine-retrosigmoid exposure as described by Anderson et al 1 The definition of what constitutes an NTR compared with an STR varies by author, with no universally agreedupon definition. Some authors have subjectively defined the residual tumor with words such as "minimal," "tiny," "small" amount, or "thin layer" of residual tumor, as defined by the operative surgeon.…”
Section: Surgical Approach and Extent Of Resectionmentioning
confidence: 99%
“…The enlarged translabyrinthine approach in VS surgery has the advantages of a low rate of morbidity and a short hospital stay, and in our opinion this is the best approach for the removal of large VSs. 3,31 Our policy for incomplete resections is to try to achieve NTR in as many cases as possible and proceed to an STR only in the remaining cases. All patients undergo follow-up for 7-10 years.…”
Section: Management Algorithmmentioning
confidence: 99%